MiR-1587 Regulates DNA Damage Repair and the Radiosensitivity of CRC Cells via Targeting LIG4 - Liu, Ruixue; Shen, Liping; Lin, Chuxian; He, Junyan; Wang, Qi; Qi, Zhenhua; Zhang, Qingtong; Zhou, Meijuan; Wang, Zhidong (Dose-response, 2020)
DNA is subject to a range of endogenous and exogenous insults that can impair DNA replication and lead to DNA double-strand breaks (DSBs). The repair capacity of cancer cells mediates their radiosensitivity, but the roles of miR-1587 during radiation resistance are poorly characterized. In this study, we explored whether miR-1587 regulates the growth and radiosensitivity of colorectal cancer (CRC) cells through its ability to regulate DNA Ligase4 (LIG4). We found that CRC cells in which miR-1587 was overexpressed inhibited cell growth and promoted apoptosis through increasing DSBs and promoting cell cycle arrest. We found that overexpression of miR-1587 significantly inhibited LIG4 messenger RNA and protein expression and further revealed the ability of miR-1587 to directly bind to the LIG4-3′-untranslated region through dual-luciferase reporter assays. More notably, miR-1587 mimics increased the radiosensitivity of CRC cells. Taken together, we show that miR-1587 overexpression enhances the formation of DSBs, arrests CRC cell growth, and enhances the radiosensivity of CRC cells through the direct repression of LIG4 expression. These results reveal novel roles for miR-1587 during DNA damage repair and the radiosensivity of CRC cells. This highlights miR-1587 as a novel therapeutic target for CRC.